Development Status of Digital Economy in Northeast Asian Countries and China’s Opportunities - Linlin, Song (Mongolian Journal of International Affairs, 2023)
With the vigorous development of digital technology, the development of the digital economy has become an important component of the global economy. Against the background of negative growth of major global economies hit hard by the COVID-19 epidemic, the steadily rising digital economy has become a key force to boost the global economy and an important engine to promote global economic development. Northeast Asian countries should use the dividends released by the digital economy to promote the coordinated development of digital technology innovation within the region, respond to technological revolution and industrial transformation, and build new international competitive advantages. This article provides a detailed overview of the current development status of digital economy in various countries in Northeast Asia, analyzes the challenges faced by countries in the region in developing cross-border digital economic and trade cooperation from three aspects: political mutual trust, digital divide, and network security. It further proposes to build a cross-border digital service trade platform in Northeast Asia, establish a China North Russia Far East digital free trade zone, so as to promote the deepening of cooperation and common development in digital trade within the region.